Potentially inappropriate medication use and associated factors in residents of long-term care facilities: A nationwide cohort study - Jang, Suhyun; Ah, Young-Mi; Jang, Sunmee; Kim, Yeji; Lee, Ju-Yeun; Kim, Jung-Ha (Frontiers in Pharmacology, 2023)
Background: Residents in long-term care (LTC) facilities (LTCFs) may have multimorbidity and be unable to self-administer medication. Thus, due to the risk of potentially inappropriate medications (PIMs), epidemiological studies on PIM use and its associated factors should be conducted to ensure safe medication use for residents in LTCFs. Objective: We evaluated PIM use among residents of LTCF and the associated factors in residents of LTCFs in Korea using a nationwide database. Methods: This cross-sectional study used the Korea National Health Insurance Service Senior Cohort (KNHIS-SC) database 2.0 of the National Health Insurance Service (NHIS), a single public insurer in Korea. We analyzed older adults aged ≥65 years who were residents of LTCFs in 2018, using the KNHIS-SC database. The 2019 American Geriatrics Society (AGS) Beers criteria was used for PIM identification. The prevalence of PIM use was defined as the proportion of LTCF residents who received PIM prescriptions at least once. We evaluated the frequency of prescriptions, including PIMs, and determined the most frequently used PIMs. We also conducted a multivariable logistic regression analysis to identify the factors associated with PIM use. Results: The prevalence of PIM among the LTCF residents was 81.6%. The prevalence of PIM was 74.9% for LTC grades 1 or 2 (high dependence) and 85.2% for LTC grades 3–5 (low dependence). Quetiapine was the most frequently prescribed PIM, followed by chlorpheniramine. The low dependence level was significantly associated with PIM use (odds ratio of LTC grades 3–5: 1.49, 95% confidence interval 1.32–1.68, reference: LTC grades 1 or 2); moreover, the number of medical institutions visited, and medications emerged as primary influencing factors. Conclusion: Most LTCF residents were vulnerable to PIM exposure. Furthermore, exposure to PIMs is associated with LTC grade. This result highlights the need for comprehensive medication management of LTCF residents.